CÂNDIDO PORTINARI'S IMAGETIC PRODUCTIONS AS PEDAGOGICAL RESOURCE TO SCHOOL PHYSICAL EDUCATION (Fiep Bulletin - online, 2014)
The profusion of thin and young corporal archetypes, with definite muscles made the athletical physical form became a referencial of beauty in the occidental societies. To contribute for the dismantling of unreachable symbols of perfection, the diversity of the corporal representations in Cândido Portinari's work is proposed. Applied in the curricular programs for High School, his pictorial registers are an interesting didactic resource for the demystification of the ideal corporal form. The pedagogical potentiality of the visual arts makes possible the enrichment of the process of construction of the knowledge under the historiccritical perspective, making the process of instrumentalization become more attractive to the students. In front of its capacity to excite significant perceptions, an interaction between the corporal representations in Portinari's production and the contemporary meanings of corporeity is suggested, once this problematic constitutes one of the study objects of the Physical Education. On methodological terms, the work is based on the bibliographical inquiry and the analysis of some paintings that contemplate the thematic of the body. It's proposed a reading of the internal logic and a comparative examination with other contemporary images which illustrate the homogeneity of the aesthetic standards. An observation concerning the compositive elements of the selected paintings, such as the subject, the technique, the forms of representation of space and light, the symbolism expressed in the aesthetic elements, the style and a personal interpretation for each studied screen must be done. In thesis, an alteration in the relations that involve the body, from reflections in the school context is considered. With the use of the art in this environment, it's expected that the principles of the dictatorship of the body can be clarified and that subsidies for a critical confrontation with the reality are appropriated by the students.
Keywords: Body and Art; Physical Education; Pedagogical Intervention